2017
DOI: 10.7554/elife.24901
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline blockade specifically enhances metacognitive performance

Abstract: Impairments in metacognition, the ability to accurately report one’s performance, are common in patients with psychiatric disorders, where a putative neuromodulatory dysregulation provides the rationale for pharmacological interventions. Previously, we have shown how unexpected arousal modulates metacognition (Allen et al., 2016). Here, we report a double-blind, placebo-controlled, study that examined specific effects of noradrenaline and dopamine on both metacognition and perceptual decision making. Signal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 67 publications
6
82
1
1
Order By: Relevance
“…Rodent studies showed that one-shot learning can occur with noradrenergic input to the hippocampus (Wagatsuma et al, 2018). More generally, a role for noradreline in confidence-weighted learning is consistent with the fact that increased pupil size co-occurs with increased updating (Nassar et al, 2012) and reset of current strategies (Devauges and Sara, 1990), and that more volatile learning contexts are associated with larger pupil size (Pulcu and Browning, showing that manipulation of noradrenergic activity impacts the estimation of confidence in a decision task (Hauser et al, 2017), learning dynamics when unexpected changes occur (Marshall et al, 2016) and the effect of surprise on update (Jepma et al, 2016(Jepma et al, , 2018.…”
Section: Discussion (1500)mentioning
confidence: 70%
“…Rodent studies showed that one-shot learning can occur with noradrenergic input to the hippocampus (Wagatsuma et al, 2018). More generally, a role for noradreline in confidence-weighted learning is consistent with the fact that increased pupil size co-occurs with increased updating (Nassar et al, 2012) and reset of current strategies (Devauges and Sara, 1990), and that more volatile learning contexts are associated with larger pupil size (Pulcu and Browning, showing that manipulation of noradrenergic activity impacts the estimation of confidence in a decision task (Hauser et al, 2017), learning dynamics when unexpected changes occur (Marshall et al, 2016) and the effect of surprise on update (Jepma et al, 2016(Jepma et al, , 2018.…”
Section: Discussion (1500)mentioning
confidence: 70%
“…Previous research has demonstrated that metacognitive efficiency is affected by fatigue (Maniscalco, McCurdy, Odegaard, & Lau, 2017), working memory demands (Maniscalco & Lau, 2015), and can be enhanced pharmacologically via noradrenaline blockade (Hauser et al, 2017). All of these previous findings rely on taxing subjects' "resources" for metacognition.…”
Section: Discussionmentioning
confidence: 91%
“…The hierarchical model proposes that metacognition and primary decision-making are two distinct cognitive processes: the primary decision-making is implemented at a first order, while a metacognitive process access both sensory evidence for the decision-making and other sources of information to form a judgement (Fleming & Daw, 2017). Many studies have reported such dissociation between metacognition and decision-making, with the PFC playing a central role in the hierarchical monitoring (Allen et al, 2017;Bang et al, 2019;Fleming et al, 2014;Hauser et al, 2017b;Qiu et al, 2018;Rounis et al, 2010;Shekhar and Rahnev, 2018).…”
Section: Discussionmentioning
confidence: 99%